Didactic Audiovisual Translation (DAT) as a Resource in Teacher Training: A Case Study - Tinedo-Rodríguez, Antonio-Jesús; Fernández-Costales, Alberto (Didáctica. Lengua y Literatura, 2025)
Educational research is a key skill in teacher training and can contribute to train more reflective teachers who are able to provide solutions that improve the learning process. The present study is part of a training program that addresses the teaching of a pedagogic technique, Didactic Audiovisual Translation (DAT), and the research methods associated with it. In DAT, Audiovisual Translation (AVT) modalities such as subtitling or dubbing are used as a teaching resource in language learning. The current paper is intended to explore the perception of future language teachers in secondary education about the need to be trained in educational research, and to analyze the major challenges posed by educational research in language teaching, particularly in those contexts where DAT is used as a teaching resource. The study takes a sample of 37 Modern Language students at a Spanish university who underwent an educational intervention for 3 months. A questionnaire with closed and open-ended responses was used to collect data, and descriptive and correlation analyses were performed. The main findings show that participants value the contextualized learning of educational research very positively and highlight the motivational factor that acquiring these skills through the design of research and innovations for DAT represents.
Keywords: Didactic audiovisual translation; Educational research; Language teaching; Teacher training; Teaching competences